Horton hears a Who! - Jones, Chuck, 1912-2002.; Geisel, Theodor Seuss, 1904-1991.; Seuss, Dr.; Washam, Ben.; Conried, Hans.; Chuck Jones Enterprises; MGM-TV.; Cat in the Hat (Firm); Warner Home Video (Firm) (Burbank, CA : Warner Home Video, 2008)
Horton is a the lovable elephant who tries to protect tiny creatures on a speck of dust. It seems that he is the only one who can hear the tiny people of the tiny planet.
Title from container.
Originally broadcast on television in 1970.
Special features: The best of Dr. Seuss: "Butter battle book," "Daisy-head Mayzie,' and 'Horton hatches the egg!'
Editor, Jim Faris ; music, Eugene Poddany ; production designer, Maurice Noble.
Voice: Hans Conried.
DVD, region 1; Dolby Digital surround stereo.; standard version; dual-layer.
Keywords: Elephants -- Fiction -- Juvenile films; Dust -- Fiction -- Juvenile films; Planets -- Fiction -- Juvenile films; Animated films; Short films; Fantasy films; Children's films; Films for the hearing impaired; French language materials; Spanish language materials